Community participation approaches to rural development in Ghana - a study of Fanteakwa District in the Eastern Region - Adinku, Ebenezer Kofi Narh (2012)
A Thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirement for the award of the Degree of Master of Science in Development Policy and Planning.